Electroluminescent optical fiber sensor for detection of a high intensity electric field - Pustelny, Tadeusz Piotr (Photonics Letters of Poland, 2020)
On-line testing of high power electromagnetic devices is one of the most important problems of modern industrial metrology. In the paper, the results of experimental investigations of the electric field optical fiber sensor based on the electroluminescent phenomena are presented. The electro¬luminescent effect is observed in some composite semicon¬ductors, among others in zinc sulfide ZnS crystals. In our investigations, the used ZnS crystal was doped with copper Cu atoms as activators. The concentration of activator in the ZnS crystal was about 5.10-4 [g/g]. According to plans of investi¬gations of the elaborated electroluminescent sensor, the spectral properties as well as the intensity of light emission in sinusoidal alternating electric field were tested. Full Text: PDF References: K.T.V. Grattan, Fiber Optic Fluorescence Thermometry, Chapman and Hall, London, 1996 [CrossRef] K. Kyuma, S. Tai, T. Sawada, "Fiber-optic instrument for temperature measurement", J. Quntum. Electronics, 73(3), 1997 [CrossRef] A. Brief, J. Chem. Educ., 88(6), 731 (2011). [CrossRef] T. Pustelny, B. Pustelny, "Investigation of electroluminophores for their practical application in optical fibre sensor technology", Opto-Electronics Rev.,10(3), 193 (2002). [CrossRef] A.Wrzesinska, Photo- and electroluminophore, Wroclaw, PWN Press, 1988, (in polish) [DirectLink] K.A. Franz, W.G. Kehr, "Luminescent Materials", Ullmans Encyclopedie of Industral Chemistry, Wiley-VCH, Veinhen, 2008 [CrossRef] A.G. Milnes, Deep Impurities In Semiconductors, A Willey-Interscience Publication, Toronto, 1993 [DirectLink] M. Aven, J.S. Prener, Physics and Chemistry of II-VI Compounds, North-Holland Publishing Company - Amsterdam, 1993 [DirectLink] P.K. Cheo, Fiber Optics Devices and Systems, Prentice-Hall, 1985 [CrossRef] D. Randall, Fluorescence and Phosphorescence, Grown, Oxford, 2007. [CrossRef] M. Koen, Photoconductivity of Semiconductors, Edited by Parks, New York, 1996 [CrossRef] K.R. Murphy, C.A. Stedmon, Annal. Methods, 6(3), 658, (2014) [CrossRef] T. Pustelny, K. Barczak, K. Gut, J. Wojcik, "Special optical fiber type D applied in optical sensor of electric currents", Optica Applicata, 34(4), 531 (2004). [DirectLink] K. Barczak, T. Pustelny, D. Dorosz, J. Dorosz, "Polarization maintaining fibers for application in magnetic field measurements", Europ. Phys. Journal: S.T., 154, 11, (2008) [CrossRef]